Analysis of Critical Thinking Ability of Class X Students' of SMA Negeri 3 Ngabang in Solving Questions Systems of Linear Equations in Three Variables Judging from Gender - Theresia, Theresia; Rif'at, Mohamad; Siregar, Nurfadilah; Sugiatno, Sugiatno; Hartoyo, Agung (Budapest International Research and Critics University, 2024)
This study aims to analyze the differences in critical thinking skills between male and female students in solving Three Variable Linear Equation System (SPLTV) problems in class X at SMA Negeri 3 Ngabang. The research method used is descriptive quantitative with a comparative approach. Data were collected from SPLTV test scores of 12 students, consisting of 6 male students and 6 female students. The results of the study showed significant variations between students based on gender. Female students demonstrated excellent performance across various critical thinking skill indicators, including conceptual understanding, analysis and interpretation, evaluation and reasoning, creativity and expertise, communication and collaboration, as well as perseverance and persistence. Male students also showed excellent performance, but there was greater variation in their abilities. Although the average scores of male students were slightly higher, their score distribution was more diverse, with some students performing exceptionally well and others performing lower. Factors influencing these differences include conceptual understanding, analysis and interpretation, evaluation and reasoning, creativity and expertise, communication and collaboration, as well as perseverance and persistence. This study indicates that female students generally have more consistent performance across critical thinking skill indicators compared to male students.